PENGARUH CORPORATE GOVERNANCE TERHADAP HUBUNGAN STRUKTUR MODALDAN NILAI PERUSAHAAN PADA PERUSAHAAN FOOD AND BEVERAGE DI BEI TAHUN 2005 -2009 - Nuryati . (STIE AUB Surakarta, 2013)
This research aim to find out; 1). the influence of the capital structure variable that measure with long term debt to total assets and debt to equity ratio to corporate governance variable. 2). The influence of the capital structure variable that measure with long term debt to total assets and debt to equity ratio on the firm valueb variable that measure with Tobin’s Q. 3). the influence of the corporate governance variable on the firm value that measure with Tobin’s Q. Purposive sampling method had been used to take these sample, and obtained 41 companies sample in observation time. Result showed: 1). The capital structure variable that measure did not effect to the corporate governance variable. 2). The capital structure variable that measure with long term debt to total assets did not effect to a firm value variable that measure with Tobin’s Q. but debt to equity ratio had negative effect to firm value variable that measure with Tobin’s Q. 3). The corporate governance did not effect to firm value variable that measure with Tobin’s Q.4). Direct influence of capital structure variable to firm value variable that measure with Tobin’s Q was bigger that at indirect influence. 5). The moderating variable, corporate governance is better than the corporate governance as intervening variable. Keyword : the capital structure, corporate governance and firm value.